Policies for Interference and Affinity-Aware Placement of Multi-tier Applications in Private Cloud Infrastructures - L. Ludwig, Uillian; F. Kirchoff, Dionatrã; B. Cezar, Ian; A. F. De Rose, César (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2017)
Multi-tier is one of the most used architectures to create applications and easily deploy them to the cloud. In the literature, there are a great number of research works focusing on the placement of these applications. While some of these works take into consideration performance, most of them are concerned about reducing infrastructure costs. Besides, none of them take into consideration the interference and network affinity characteristics. Therefore, in this work, we create placement policies that aim to improve the performance of multi-tier applications by analyzing the interference and network affinity characteristics of each tier. These characteristics work as a force pushing tiers closer or farther depending on the interference and affinity levels. Moreover, by using these placement policies, we show that multi-tier applications can better utilize the infrastructure, using the same infrastructure but with an improved performance.